Secondary bacterial infections and antibiotic resistance among tungiasis patients in Western, Kenya. - Ruth Monyenye Nyangacha; David Odongo; Florence Oyieke; Missiani Ochwoto; Richard Korir; Ronald Kiprotich Ngetich; Gladys Nginya; Olipher Makwaga; Christine Bii; Peter Mwitari; Festus Tolo (PLoS Neglected Tropical Diseases)
Tungiasis or jigger infestation is a parasitic disease caused by the female sand flea Tunga penetrans. Secondary infection of the lesions caused by this flea is common in endemic communities. This study sought to shed light on the bacterial pathogens causing secondary infections in tungiasis lesions and their susceptibility profiles to commonly prescribed antibiotics. Participants were recruited with the help of Community Health Workers. Swabs were taken from lesions which showed signs of secondary infection. Identification of suspected bacteria colonies was done by colony morphology, Gram staining, and biochemical tests. The Kirby Bauer disc diffusion test was used to determine the drug susceptibility profiles. Out of 37 participants, from whom swabs were collected, specimen were positive in 29 and 8 had no growth. From these, 10 different strains of bacteria were isolated. Two were Gram positive bacteria and they were, Staphylococcus epidermidis (38.3%) and Staphylococcus aureus (21.3%). Eight were Gram negative namely Enterobacter cloacae (8.5%), Proteus species (8.5%), Klebsiellla species (6.4%), Aeromonas sobria (4.3%), Citrobacter species (4.3%), Proteus mirabillis(4.3%), Enterobacter amnigenus (2.1%) and Klebsiella pneumoniae (2.1%). The methicillin resistant S. aureus (MRSA) isolated were also resistant to clindamycin, kanamycin, erythromycin, nalidixic acid, trimethorprim sulfamethoxazole and tetracycline. All the Gram negative and Gram positive bacteria isolates were sensitive to gentamicin and norfloxacin drugs. Results from this study confirms the presence of resistant bacteria in tungiasis lesions hence highlighting the significance of secondary infection of the lesions in endemic communties. This therefore suggests that antimicrobial susceptibility testing may be considered to guide in identification of appropriate antibiotics and treatment therapy among tungiasis patients.